Anacondas the hunt for the blood orchid - Harrah, Verna; Little, Dwilight ([New York] : Columbia Tristar, 2004)
The blood orchid is a rare flower that holds the secret to eternal life and a fortune to the pharmaceutical company that finds it. Led by a two-fisted soldier of fortune, a scientific expedition is sent deep into the jungles of Borneo to locate and bring back samples of the legendary plant. Battling their way upriver, the explorers brave poisonous insects, ferocious crocodiles and savage headhunters, unaware that they are being stalked by an even greater danger: a nest of giant anacondas, who'll stop at nothing to protect their breeding groud, the blood orchid's home
Title from title screen
Director of photography, Stephen F. Windon ; editors, Marcus D'Arcy, Mark Warmer ; music, Nerida Tyson-Chew ; costume designer, Terry Ryan ; production designer, Bryce Perrin
Cast: Johnny Messner, KaDee Strickland, Matthew Marsden, Eugene Byrd, Salli Richardson-Whitfield, Nicholas Gonzalez, Karl Yune, Denis Arndt, Morris Chestnut
DVD Format
Audio in English or Thai with optional English, Thai, Chinese or Korean subtitles
Keywords: Anaconda -- Drama; Snakes -- Drama